Antecedents of employee alienation and its impact on individual work performance during post-merger integration (PMI). Issue 6 (8th October 2020) - Al Hosani, Yousef; Jabeen, Fauzia; Paul, Justin; Stachowicz-Stanusch, Agata
Abstract : Purpose: The objective of this study was to examine the significant factors leading to employee alienation in post-merger integration (PMI). Design/methodology/approach: Data were collected from 482 middle- and low-level employees in two organizations in the real estate and banking sectors in the United Arab Emirates. The analysis was carried out using structural equation modeling (SEM). Findings: Organizational justice, employee commitment, organizational trust, perceived effectiveness of human resource (HR) initiatives and employee communication strategy played an important role in developing or mitigating a feeling of alienation among employees during PMI. Employee tenure in the organization affected individual work performance. Research limitations/implications: The study was limited to middle- and low-level employees and did not consider other organizational variables important in mergers. This study will help merger strategists to deliver appropriate HR practices during PMI, facilitating mitigation of uncertainties among employees and maximizing their trust and commitment. Originality/value: The study results will help organizations understand employee trust, commitment and determinants in an emerging economy.